(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article analyzes the theory of scientific views on terminology, which is one of the developing fields of linguistics. Definitions given by linguists have also been shown for the concept of term, which is the main part of terminology. Terminology is a set of terms in a certain field of knowledge or production, as well as the doctrine of the formation, composition and operation of the term.